Mass Refugee Inflow and Long-run Prosperity: Lessons from the Greek Population Resettlement - Elie Murard; Seyhun Orcan Sakalli (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
We investigate the long-term consequences of mass refugee inflow on economic develop-ment. After the Greco-Turkish war of 1919-1922, 1.2 million Greek Orthodox were forciblyresettled from Turkey to Greece, increasing the host population by more than 20% within afew months. To examine the long-term effects of this event, we build a novel geocoded datasetlocating refugee settlements across the universe of more than four thousand Greek municipali-ties that existed in 1920. Using a battery of empirical strategies relying on different margins ofspatial and temporal variation in the refugee inflow, we find that localities with a greater shareof Greek refugees in 1923 display higher level of prosperity and industrialization sixty yearsafter the event. These long-run benefits of refugees appear to be driven by the provision of newagricultural know-how and the transfer of technological knowledge in textile, which fosteredgrowth through higher diversity in complementary skills. The economic gains of the resettle-ment were lower in places where refugees were clustered in separate enclaves and where theirskills were less easily transferable due to local geographic conditions.
Keywords: O10; O43; N34; N44; 330; Refugees; Immigration; historical persistence; economic development